Comparación del impacto de agua y probiótico "EM.1" en el rendimiento y composición química del forraje verde hidropónico de maíz en Zúngaro Cocha 2023 - Sandoval Tello, Endo (2024)
The present study focused on evaluating the impact of water use and the addition of the probiotic EM.1 on the yield and chemical composition of hydroponic green forage (FVH) of corn in Zúngarococha during the year 2023. The research was carried out using a cross-sectional and prospective experimental design that allowed comparing the results obtained with and without the application of probiotics. For data analysis, statistical techniques such as Student's t-test and regression analysis were used, which allowed evaluating the relationship between the independent variables water and probiotic and the dependent variable forage yield. The results showed that the addition of the probiotic EM.1 significantly improves the yield of maize FVH, evidencing increases in dry mass and other growth parameters such as plant height, stem diameter and number of leaves. These results indicate that the implementation of probiotics is an effective tactic to improve production in hydroponic systems, promoting a more sustainable and efficient agriculture. In summary, the inclusion of the probiotic EM.1 in maize FVH not only increases productivity, but also enriches the nutritional quality of forage, which can positively influence animal feed and the sustainability of farming systems.